Diagnosis of Deviation Indicators of Distribution Network Engineering Based on Fuzzy Petri Net - Haozheng YU; Zhaolun PAN; Ke LI; Peng ZHOU; Xinzhi GUO; Huijun SUN; Jinxiong YU; Cunbin LI (Zhongguo dianli)
With the rapid development of distribution network engineering in recent years, the data of various control indicators for construction of distribution network projects has also become more diverse and complex. At the same time, it is hard to identify the deviation indicators of the distribution network projects due to the limited data processing capabilities, which leads to poor identification and location of some long-standing deviation indicators in the distribution network projects. Based on the theory of fuzzy Petri net, a diagnosis model is designed for the deviation indicators of distribution network projects, and the method for determining the real-time data of each indicator in the process of construction of the distribution network projects is analyzed. A case study is carried out for determining the deviation indicators of the distribution network project, which can provide a good reference for project management personnel to manage the distribution network engineering in a timely and effective manner.